DevOps Main Area and Core Capabilities Adopting DevOps in the Last Decade: A Systematic Literature Review - Jefri Zulkarnain; Rizki Firdaus Mulya; Tika Pratiwi; Widi Pangestuti; Fahma Inti Ilmawati (Universitas Komputer Indonesia, 2022)
DevOps is a collaboration between software development and operation that utilizes frameworks like continuous integration, microservices, continuous delivery, and continuous deployment for an agile software development process. DevOps has principles like automation, iteration, and continuous release and development. This research aims to know DevOps development in the last decade and know how potentially adopt the DevOps development process. This study uses the Systematic Literature Review (SLR) method to locate, evaluate, and summarize pertinent works that were published in the public domain between 2012-2022. The result of this review will be used by researchers and practitioners as a piece of knowledge about the DevOps core capabilities and main areas of DevOps from adopting DevOps in the last decade.